Periodic solutions of the N point-vortex problem in planar domains - Dai, Qianhui; Justus Liebig University Giessen (My University, 2014)
The N point-vortex Hamiltonian system from fluid dynamics is a prominent and representative example of a first order singular Hamiltonian system which appears in Mathematical Physics. The logarithmic singularities appearing in the Hamiltonian are of a very different type compared with those appearing in classical (e.g. celestial) mechanics. Owing to the complexity of the Hamiltonian function and the compactness problems, investigating periodic solutions of the system in planar domains is highly nontrivial. This dissertation addresses two issues related to this topic.The first issue concerns the point vortex system in the disk. The system for two vortices in the disk is completely integrable in the sense of Liouville. Appropriate canonical coordinate transformations are presented to reduce the degrees of freedom. By examining the reduced system, it is revealed that any non-asymptotic motion of two identical vortices in the disk is a superposition of a uniform rotation of the coordinate frame and a periodic motion in this rotating frame. Examples of trajectories both in the rotating frame and in the original system are plotted numerically. The existence of symmetric periodic solutions, so-called ´vortex crystals´, in the disk is also discussed. It is proved that the configurations of an open or centered N-polygon, of symmetric two N-polygons and of alternate two N-polygons with generic choice of radii or strengths exist for the system in the disk.The second part of this dissertation focuses on the N-vortex problem in general planar domains. It is proved that when all the strengths of the N vortices are the same, a stable critical point of the Robin function associated with this domain yields periodic solutions with arbitrarily small minimal period oscillating around this point. These periodic solutions are near a singularity of the phase space. Moreover, they are simple choreographies, i.e. the N vortices travel on the same circle with a phase-shift. The proof is based on a careful investigation of the behavior of the action functional near this singularity. This result applies in particular to generic bounded domains, which may be simply or multiply connected. Then it is generalized to the system of two point vortices with arbitrary non-opposite strengths. A similar result is also obtained when the logarithm function log |z1 - z2|is replaced by |z1 - z2|- alpha with alpha greater than 0.

Das Hamiltonsche N-Punktwirbel-System der Fluid-Dynamik ist ein prominentes Beispiel für ein singuläres Hamiltonsches System erster Ordnung aus der mathematischen Physik. Die logarithmischen Singularitäten der Hamiltonfunktion sind sehr verschieden von denen, die in der klassischen Mechanik (Himmelsmechanik) vorkommen. Wegen der Komplexität der Hamiltonfunktion und wegen der Kompaktheitsprobleme ist die Suche nach periodischen Lösungen in ebenen Gebieten sehr schwierig. Die Dissertation befasst sich mit zwei Fragestellungen in diesem Rahmen.Die erste Fragestellung betrifft das Punktwirbelsystem in einer Kreisscheibe. Das System von zwei Wirbeln in der Kreisscheibe ist vollständig integrierbar im Sinn von Liouville. Es werden mehrere kanonische Koordinatentransformationen angewandt, um den Freiheitsgrad zu reduzieren. Bei der Untersuchung des reduzierten Systems zeigt sich, dass jede nichtasymptotische Bewegung zweier identischer Wirbel in der Scheibe eine Superposition einer Rotation des Koordinatensystems mit einer periodischen Bewegung ist. Beispielhafte Trajektorien sowohl im rotierenden System als auch im reduzierten Originalsystem werden numerisch geplottet. Außerdem wird die Existenz symmetrischer periodischer Lösungen, sogenannter Wirbelkristalle, diskutiert. Es wird gezeigt, dass Konfigurationen offener oder zentrierter N-Polygone, symmetrischer N-Polygone und zweier phasenverschobener N-Polygone, mit allgemeinen Radien und Wirbelstärken, existieren.Der zweite Teil der Dissertation konzentriert sich auf das N-Wirbel-Problem in allgemeinen ebenen Gebieten. Wenn die Stärken aller N Wirbel gleich sind, gibt es in der Nähe eines stabilen kritischen Punkts der Robin-Funktion periodische Lösungen mit beliebig kleinen Perioden, die um diesen Punkt rotieren. Diese periodischen Lösungen sind also nahe einer Singularität der Hamiltonfunktion. Außerdem sind sie einfache Choreographien, das heißt die N Wirbel bewegen sich phasenverschoben auf einer kreisähnlichen Trajektorie. Der Beweis basiert auf einer sorgfältigen Untersuchung des Verhaltens des Wirkungsintegrals in der Nähe der Singularität. Dieses Ergebnis gilt in allgemeinen beschränkten Gebieten, die einfach oder mehrfach zusammenhängend sein können. Es wird verallgemeinert auf das System zweier Punktwirbel mit beliebigen Wirbelstärken. Ein ähnliches Ergebnis wird auch erzielt, wenn die logarithmische Singularität log |z1 - z2|ersetzt wird durch |z1 - z2|- alpha mit alpha größer als 0.
Periodische Lösungen des N-Punktwirbel-Problems in ebenen Gebieten
Keywords: point-vortex; periodic solution; ddc:510